Solution-focused brief therapy a handbook of evidence-based practice - Franklin, Cynthia (New York ; Oxford : Oxford University Press, 2011)
Therapy is frequently miscast as requiring an enormous amount of time and financial commitment, but helpful, goal-oriented therapy can produce positive results after only a few sessions. By focusing on solutions instead of problems, SFBT asks clients to set concrete goals and to draw upon strengths in their lives that can help bring about the desired change for a preferred future.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Solution-focused brief therapy